Competition for IL-2 between regulatory and effector T cells to chisel immune responses - Höfer, Thomas; Krichevsky, Oleg; Altan-Bonnet, Grégoire (Frontiers in immunology, 2012)
In this review we discuss how the competition for cytokines between different cells of the immune system can shape the system wide immune response. We focus on interleukin-2 (IL-2) secretion by activated effector T cells (Teff) and on the competition for IL-2 consumption between Teff and regulatory T cells (Treg). We discuss the evidence for the mechanism in which the depletion of IL-2 by Treg cells would be sufficient to suppress an autoimmune response, yet not strong enough to prevent an immune response. We present quantitative estimations and summarize our modeling effort to show that the tug-of-war between Treg and Teff cells for IL-2 molecules can be won by Treg cells in the case of weak activation of Teff leading to the suppression of the immune response. Or, for strongly activated Teff cells, it can be won by Teff cells bringing about the activation of the whole adaptive immune system. Finally, we discuss some recent applications attempting to achieve clinical effects through the modulation of IL-2 consumption by Treg compartment.
Gesehen am 12.11.2018